# Mathematics Class 7 – Chapter 4 – Simple Equation – Exercise – 4.2 – NCERT Exercise Solution

1. Give first the step you will use to separate the variable and then solve the equation:

(a) x – 1 = 0

Solution:

Adding 1 to both the side of given equation,

we get,

x – 1 + 1 = 0 + 1

x = 1

(b) x + 1 = 0

Solution:

Subtracting 1 to both the side of given equation,

we get,

x + 1 – 1 = 0 – 1

x = – 1

(c) x – 1 = 5

Solution:

Adding 1 to both the side of given equation,

we get,

x – 1 + 1 = 5 + 1

x = 6

(d) x + 6 = 2

Solution:

Substracting 6 to both the side of given equation,

we get,

x + 6 – 6 = 2 – 6

x = – 4

(e) y – 4 = – 7

Solution:

Adding 4 to both the side of given equation,

we get,

y – 4 + 4 = – 7 + 4

y = – 3

(f) y – 4 = 4

Solution:

Adding 4 to both the side of given equation,

we get,

y – 4 + 4 = 4 + 4

y = 8

(g) y + 4 = 4

Solution:

Substracting 4 to both the side of given equation,

we get,

= y + 4 – 4 = 4 – 4

= y = 0

(h) y + 4 = – 4

Solution:

Substracting 4 to both the side of given equation,

we get,

= y + 4 – 4 = – 4 – 4

= y = – 8

2. Give first the step you will use to separate the variable and then solve the equation:

(a) 3l = 42

Solution:

Dividing both sides of the equation by 3,

we get,

3l/3 = 42/3

l = 14

(b) b/2 = 6

Solution:

Multiplying both sides of the equation by 2,

we get,

b/2 × 2= 6 × 2

b = 12

(c) p/7 = 4

Solution:

Multiplying both sides of the equation by 7,

we get,

p/7 × 7= 4 × 7

p = 28

(d) 4x = 25

Solution:

Dividing both sides of the equation by 4,

we get,

4x/4 = 25/4

x = 25/4

(e) 8y = 36

Solution:

Dividing both sides of the equation by 8,

we get,

8y/8 = 36/8

x = 9/2

(f) (z/3) = (5/4)

Solution:

Multiplying both sides of the equation by 3,

we get,

(z/3) × 3 = (5/4) × 3

x = 15/4

(g) (a/5) = (7/15)

Solution:

Multiplying both sides of the equation by 5,

we get,

(a/5) × 5 = (7/15) × 5

a = 7/3

(h) 20t = – 10

Solution:

Dividing both sides of the equation by 20,

we get,

20t/20 = -10/20

x = – ½

3. Give the steps you will use to separate the variable and then solve the equation:

(a) 3n – 2 = 46

Solution:

In step 1 we add 2 to the both sides of the equation,

we get,

3n – 2 + 2 = 46 + 2

= 3n = 48

In step 2 we divide both sides of the equation by 3,

we get,

3n/3 = 48/3

n = 16

(b) 5m + 7 = 17

Solution:

In step 1 we subtract 7 to the both sides of the equation,

we get,

5m + 7 – 7 = 17 – 7

5m = 10

In step 2 we divide both sides of the equation by 5,

we get,

5m/5 = 10/5

m = 2

(c) 20p/3 = 40

Solution:

In step 1 we multiply both sides of the equation by 3,

we get,

(20p/3) × 3 = 40 × 3

20p = 120

In step 2 we divide both sides of the equation by 20,

we get,

20p/20 = 120/20

p = 6

(d) 3p/10 = 6

Solution:

In step 1 we multiply both sides of the equation by 10,

we get,

(3p/10) × 10 = 6 × 10

3p = 60

In step 2 we divide both sides of the equation by 3,

Then, we get,

3p/3 = 60/3

p = 20

4. Solve the following equations:

(a) 10p = 100

Solution:

Dividing both sides of the equation by 10,

we get,

10p/10 = 100/10

p = 10

(b) 10p + 10 = 100

Solution:

Subtracting 10 to the both sides of the equation,

we get,

10p + 10 – 10 = 100 – 10

10p = 90

Now,

Dividing both sides of the equation by 10,

we get,

10p/10 = 90/10

p = 9

(c) p/4 = 5

Solution:

Multiplying both sides of the equation by 4,

we get,

p/4 × 4 = 5 × 4

p = 20

(d) – p/3 = 5

Solution:

Multiplying both sides of the equation by – 3,

we get,

– p/3 × (- 3) = 5 × (- 3)

p = – 15

(e) 3p/4 = 6

Solution:

Multiplying both sides of the equation by 4,

we get,

(3p/4) × (4) = 6 × 4

3p = 24

Now,

Dividing both sides of the equation by 3,

we get,

3p/3 = 24/3

p = 8

(f) 3s = – 9

Solution:

Dividing both sides of the equation by 3,

we get,

3s/3 = -9/3

s = -3

(g) 3s + 12 = 0

Solution:

Substracting 12 to the both sides of the equation,

we get,

3s + 12 – 12 = 0 – 12

3s = -12

Now,

Dividing both sides of the equation by 3,

we get,

3s/3 = -12/3

s = – 4

(h) 3s = 0

Solution:

Dividing both sides of the equation by 3,

we get,

3s/3 = 0/3

s = 0

(i) 2q = 6

Solution:

Dividing both sides of the equation by 2,

we get,

2q/2 = 6/2

q = 3

(j) 2q – 6 = 0

Solution:

Adding 6 to the both sides of the equation,

we get,

2q – 6 + 6 = 0 + 6

2q = 6

Now,

Dividing both sides of the equation by 2,

we get,

2q/2 = 6/2

q = 3

(k) 2q + 6 = 0

Solution:

Subtracting 6 to the both sides of the equation,

we get,

2q + 6 – 6 = 0 – 6

2q = – 6

Now,

Dividing both sides of the equation by 2,

we get,

2q/2 = – 6/2

q = – 3

(l) 2q + 6 = 12

Solution:

Subtracting 6 to the both sides of the equation,

we get,

2q + 6 – 6 = 12 – 6

2q = 6

Now,

Dividing both sides of the equation by 2,

we get,

2q/2 = 6/2

q = 3

👍👍👍

error: